The importance of art: reflections and thoughts about the sacred concert conducted in the municipality of Escada-PE / A importância da arte: reflexões e pensamentos sobre o concerto sacro realizado no município de Escada-PE - Dimison Cesar Vieira Gomes; Ana Lucia Gomes Cavalcanti Neto (Universidade Estadual de Alagoas, 2019)
This article aims to describe reflections and thoughts about the importance of Art through the experience during the presentation of the Sacred Concert, held in the municipality of Escada-PE, on June 9, 2018. During and shortly after the end of this event , information was recorded from the reactions and comments of the public present. During the analysis of the collected elements, there was a comparative discussion with those divulged by several authors involved with the topic discussed. In this context, this experience makes it possible to perceive that musical appreciation can become an important constructive process of musical learning, personal and sociocultural interrelations, through elements that promote the construction of meanings inherent and delineated to the public.